CAN you Feel it? An Immersive and Tangible Car Simulation Experience - Pereira, Carlos Gabriel; Ohara, David; Neto, Amadeo; Nunes, Fatima; Teixeira, João Marcelo (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
We present a Work-in-Progress (WiP) Virtual Reality (VR) system that turns a real vehicle into an input controller for its own 3D twin. Using a commodity On-Board Diagnostics II (OBD-II) Bluetooth adapter attached to a BYD Dolphin Plus, we extract real-time steering wheel angle, longitudinal acceleration, and brake status and forward them to a Meta Quest 3 headset. In the current prototype, a PC acts as a bridge between the OBD-II link and the Head Mounted Display (HMD); the VR application, implemented in Unity, renders a full-scale digital model registered to the real car via spatial anchors, allowing users to physically touch the real vehicle while seeing and interacting with its virtual counterpart. We report feasibility results of Bluetooth protocol inspection for the BYD Dolphin Plus, low-latency telemetry forwarding, and anchor stability indoors. We outline the remaining steps to remove the PC bridge and connect the OBD-II adapter directly to the Quest 3, enabling standalone operation. Our findings indicate that real-vehicle telemetry can drive a collocated VR twin with low end-to-end latency, supporting the broader vision of using the physical car as a tangible interface in training and demonstration scenarios.